SP1-Mediated Upregulation of Long Noncoding RNA ZFAS1 Involved in Non-syndromic Cleft Lip and Palate via Inactivating WNT/β-Catenin Signaling Pathway - Chen, Shiyu; Jia, Zhonglin; Cai, Ming; Ye, Mujie; Wu, Dandan; Wan, Teng; Zhang, Bowen; Wu, Peixuan; Xu, Yuexin; Guo, Yuntao; Tian, Chan; Ma, Duan; et al. (Frontiers in Cell and Developmental Biology, 2021)
Non-syndromic cleft lip and palate (NSCLP) is one of the most common congenital malformation with multifactorial etiology. Although long non-coding RNAs (lncRNAs) have been implicated in the development of lip and palate, their roles in NSCLP is not fully elucidated. This study aimed to investigate how dysregulated lncRNAs contribute to NSCLP. Using lncRNA sequencing, bioinformatics analysis and clinical tissue sample detecting, we identified lncRNA ZFAS1 was significantly upregulated in NSCLP. The upregulation of ZFAS1 mediated by SP1 transcription factor(SP1) inhibited expression levels of Wnt family member 4(WNT4) through the binding with CTCF, subsequently inactivating WNT/β-catenin signalling pathway, which has been reported to play a significant role on the development of lip and palate. Moreover, in vitro, the overexpression of ZFAS1 inhibited cell proliferation and migration in human oral keratinocytes and human umbilical cord mesenchymal stem cells (HUC-MSCs), and also repressed chondrogenic differentiation of HUC-MSCs. In vivo, ZFAS1 suppressed cell proliferation and numbers of chondrocyte in the zebrafish ethmoid plate. In summary, these results indicated that ZFAS1 may be involved in NSCLP by affecting cell proliferation, migration and chondrogenic differentiation through inactivating WNT/β-catenin signalling pathway.